The Influence of Service, Attraction, and Facilities on the Visitor Loyalty of Halal Tourism in Medan City (Case Study of Maimun Palace) - Hafid Anshari; Slamet Widodo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of service quality, destination attraction, and supporting facilities on visitor loyalty in the context of halal tourism at Maimun Palace, Medan City. Employing a quantitative approach with an associative research design, the study involved 254 respondents selected using the Slovin formula from a total population of 689 visitors recorded in April 2025. Data were collected through a structured questionnaire using a Likert scale and analyzed using SPSS software. The findings reveal that each independent variable—service, attraction, and facilities—has a positive and significant effect on visitor loyalty. Furthermore, the simultaneous analysis confirms that the combination of these three factors significantly influences loyalty among visitors to the halal tourism destination. These results align with the Customer Satisfaction Theory, which posits that positive experiences related to service delivery, destination appeal, and the availability of appropriate facilities contribute to higher levels of satisfaction, ultimately fostering loyalty. The implications of this study suggest that halal tourism destination managers should prioritize enhancing service quality, preserving the cultural and historical appeal of attractions, and ensuring the availability of facilities that meet the specific needs of Muslim tourists. By doing so, destinations like Maimun Palace can cultivate sustainable visitor loyalty, which is essential for long-term tourism development and competitiveness in the halal tourism sector. This research contributes to the growing body of literature on halal tourism by empirically validating the role of service, attraction, and facilities in shaping visitor loyalty. Future studies are recommended to explore additional variables such as religious compliance, digital engagement, and cultural sensitivity to provide a more comprehensive understanding of loyalty drivers in halal tourism contexts.